A survey on self-medication for the prevention or treatment of COVID-19 and distrust in healthcare of veterans in a primary care setting in the United States. (December 2022) - Amenta, Eva; Grigoryan, Larissa; Dillon, Laura; Hines-Munson, Casey; Van, John; Trautner, Barbara
Background: The SARS-CoV-2 (COVID-19) pandemic brought the public overwhelming and conflicting information. Rates of trust in healthcare professionals have been declining among laypersons over the past five decades. In this setting, we sought to evaluate the use of medications, both with or without a prescription, to prevent and treat SARS-CoV-2 as well as trust in healthcare among patients in a primary care clinic. Design: We surveyed 150 veterans in primary care clinic waiting rooms at a large southwestern tertiary care Veterans Affairs hospital. This survey was performed in March–November 2021. Methods: The survey asked about respondents' demographics, use of medications, nutritional supplements, and other remedies for the prevention and treatment of COVID-19, perceived access to care using Agency for Healthcare Research and Quality (AHRQ) Consumer Assessment of Healthcare Providers and System (CAHPS), overall health status, and barriers to medical appointments in the last 12 months. Distrust was measured using the Revised Health Care Distrust scale. We used univariate and multivariate linear regression analyses to study predictors of distrust to healthcare. Results: Forty-two (28%) of 150 respondents reported taking an agent for the prevention of COVID-19, while 4% reported storing antibiotics for the treatment of COVID-19, if diagnosed. Medications were obtained from medical providers, US stores or markets, the Internet, home stockpiles, and other countries. Medications with potentially harmful effects taken for the prevention and treatment of COVID-19 included hydroxychloroquine, pseudoephedrine, and antibiotics. Among those surveyed, the mean (SD) on the health system distrust score was 2.2 (0.6) on a scale of 1–5, with 5 indicating higher distrust. Younger age, self-reported poor health, lack of a regular physician, and self-reported poor access to care were independently associated with distrust in healthcare. Conclusion: Self-medication to prevent COVID-19 infection with unproven therapies was common among respondents, as was some level of distrust in the healthcare system. Access to care was one of the modifiable factors associated with distrust. Future studies may explore whether improving trust may moderate self-treatment behavior and storage of potentially harmful medications. Plain Language Summary: Self-Medication Habits and Trust in Healthcare Among Patients in a Primary Care Setting in the United States The public has received information from many different sources on COVID-19. Trust in healthcare leadership has also been impacted. We studied self-medication habits to prevent or treat COVID-19 among a group of primary care patients in a large hospital system in the Southwest United States. We also explored these patients' trust in their healthcare system. We asked people waiting in primary care clinic waiting rooms whether they had taken any medications, nutritional supplements, or other remedies to prevent or treat COVID-19. We also asked people whether they stored medications in the event that they were diagnosed with COVID. The survey explored patients' trust in the healthcare system through a validated trust survey tool. The survey also assessed basic demographic information, health literacy, access to care, and self-reported health status. These survey answers were analyzed to see whether there was an association between trust in healthcare and other factors including self-medication habits, access to care, demographics, or perceived health. This study found that over 25% of the 150 people surveyed had taken a medication, nutritional supplement, or remedy in an attempt to prevent COVID. We found that some people were taking potentially harmful medications, including hydroxychloroquine, pseudoephedrine, and antibiotics. We found that patients' distrust score was 2.2 on a scale of 1–5 (5 is associated with higher distrust). Self-medication for the prevention or treatment of COVID was not associated with distrust; however, younger age, self-perceived lack of access to healthcare, self-perceived poor overall health, and not having a regular doctor were predictors for lower trust. This information provides a basis to further study self-medication habits as well as ways to improve trust in the healthcare system.